Imaging findings of ovarian leiomyosarcoma with histopathologic correlations. (May 2019) - Fischetti, Aldo; Rutigliani, Mariangela; Romano, Nicola; Marinaro, Eugenio Lucio; Puppo, Cristina; Gorlero, Franco; Melani, Enrico Francesco; Rollandi, Gian Andrea
Abstract: Leiomyosarcoma (LMS) is a malignant mesenchymal tumor deriving from smooth muscle. Ovarian LMS is exceedingly rare and only few reports have been reported in literature. The article illustrates a case of ovarian leiomyosarcoma in a 61-year-old woman, describing CT and MRI features correlated to histopathologic findings. LMS should be included in the differential diagnosis of solid and multiloculated ovarian lesions, in particular in post-menopausal women.